Surface elasticity-based modeling of rotating functionally graded nanoshafts in thermal environments. Issue 12 (1st December 2016) - Kiani, Keivan
ABSTRACT: Thermoelastic field analysis of a rotating functionally graded nanoshaft (RFGNS) in thermal environments is of interest. The governing equations of the rotating nanoshaft with varying material properties along the radial direction are obtained. Two nonclassical boundary conditions, namely, fixed-free and free–free, are established accounting for the surface energy effect. Using finite element method and Hamilton's principle, the thermoelastic field within RFGNS is evaluated. The effects of power-law index, aspect ratio, temperature, angular velocity of the RFGNS, and surface energy on the displacements and stresses are displayed in detail.